Use of Visual Media (Images) to Improve Students' Abilities in Arabic Language Lessons Tarkib Material Dhamir - Arif, Muh; Suriani; Rudi Tarenre (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2024)
This research is action research with data collection techniques through observation, tests, and documentation using a spiral model through 4 (four) stages or procedures, namely planning, implementing actions, observation and reflection. The analysis technique is data in the form of quantitative data and qualitative data consisting of pre-cyclical test results, cycles I and II. The source of data from this research is class X students. 10 Madrasah Aliyah Negeri Pinrang for the 2022/2023 academic year totaling 16 people which will be held for 3 (three) months in August, September to October 2022. From the results of the study, it can be concluded that learning Arabic on tarkib dhamir material using visual media (images) can improve the results and enthusiasm for learning of class X students. 10 Madrasah Aliyah Negeri Pinrang. This can be seen from the pre-cycle data with an average of 69.6, cycle I with an average of 73.8, and cycle II which is increasingly increasing with an average of 80.